2021
DOI: 10.28982/josam.948316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and laboratory parameters in patients with migraine or tension-type headaches: A case-control study

Abstract: All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…In terms of gender characteristics, the most sufferers were found in women, both in migraineurs and TTH sufferers. This is in line with previous research conducted by Yilmaz et al (2021) and Arikan et al (2020) which showed that women suffer from migraines and TTH more compared to men [ 4 , 17 ]. Epidemiologically, both migraine and TTH are more common in women than men with a ratio of 3: 1.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of gender characteristics, the most sufferers were found in women, both in migraineurs and TTH sufferers. This is in line with previous research conducted by Yilmaz et al (2021) and Arikan et al (2020) which showed that women suffer from migraines and TTH more compared to men [ 4 , 17 ]. Epidemiologically, both migraine and TTH are more common in women than men with a ratio of 3: 1.…”
Section: Discussionsupporting
confidence: 93%